The British and the Vietnam War : their way with LBJ - Tarling, Nicholas (NUS Press, 2017)
"During the presidency of Lyndon Johnson, the British government sought to avoid escalation of the war in Vietnam and to help bring about peace. The thinking that lay behind these endeavours was often insightful and it is hard to argue that the attempt was not worth making, but the British government was able to exert little, if any, influence on a power with which it believed it had, and needed, a special relationship. Drawing on little-used papers in the British archives, Nicholas Tarling describes the making of Britain's Vietnam policy during a period when any compromise proposed by London was likely to be seen in Washington as suggestive of defeat, and attempts to involve Moscow in the process over-estimated the USSR's influence on a Hanoi determined on reunification."